THE IMPACT OF SHIFTING TOWARDS ECO-FRIENDLY TRANSPORTATION AT THE UNIVERSITY OF BAGHDAD, AL-JADRIYA CAMPUS (UBAC) - Firas ALRAWI; Ali ALALI; Sarah ALAA; Shurooq SAAD; Araz AMEER (Scientific Journal of Silesian University of Technology. Series Transport)
In recent years, the UBAC has seen severe traffic congestion, resulting in various environmental and traffic problems at the university and its environs. This congestion was due to the significant expansions in buildings andan increase in the number of colleges in addition to the extensive use of private transport modes by students and university employees. This research was an attempt to find a solution for transportation problems in the UBAC, through studying the current transportation system inside the campus, and then suggesting alternatives to enhance the situation in the Campus and its environs as well. The study solutions focused on replacing the current diesel buses with battery-electric buses and restricting some of the private cars toward the Campus. This study supposes this transformation will reduce the CO2 emissions by (54%) in the morning peak hours and by (64%) in the afternoon peak hours, enhance the Passenger Car Unit (PCU) by (31%) in the morning peak hours and by (41%) in the afternoon peak hours, and will improve parking capacity by 114% inside the campus.